The influence of N-acetylneuraminic acid on the properties of human orosomucoid. - Friedman, M L (1986)
Little is known of the relationships that may exist among the three principal functionalities of glycoproteins. Orosomucoids of closely defined N-acetylneuraminic acid content were examined for evidence of influence of N-acetylneuraminic acid content on the physical properties of the glycoprotein. Fluorescence spectroscopy gave no indication of conformational change in the protein core upon desialylation. Small changes in the chromatographic partition coefficient, sigma, and thermal stability, Td, are interpreted to reflect loss of water of hydration and increased glycan stem-protein interaction without a major repositioning of the chains. Ligand-binding measurements indicate no alteration in the hydrophobic binding domain and a possible interaction between chlorpromazine and N-acetylneuraminic acid. All changes seen are progressive and occur through a region where changes in biological activity are not found. It is suggested that the dependence of biological activity on N-acetylneuraminic acid content in orosomucoid reflects, not coupled changes in protein conformation, but a charge-density-related interaction such that, below a contribution of four or five N-acetylneuraminic acid residues, activity is modified.